2019
DOI: 10.11648/j.ajbls.20190705.11
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Birth Injuries in a Tertiary Hospital in Enugu, Nigeria

Abstract: Background: Birth injury is defined as structural damage of a newborn secondary to mechanical forces that occur during labor and/or delivery. This study determined the incidence, risk factors and outcome of birth injury. Methodology: This was an observational study of birth injuries in neonates, over a period of one year, carried out at a tertiary hospital in Enugu, south east, Nigeria. Results: Out of the 1,735 births recorded during the period of the study, there were 19 cases of birth injuries. This gave an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 15 publications
3
15
4
2
Order By: Relevance
“…There was male preponderance in the present study which was in conformity with several studies in Nigeria [4,5,[16][17][18] and India. [11,19] In contrast, Ray et al [20] and Pinto et al [21] reported female preponderance.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…There was male preponderance in the present study which was in conformity with several studies in Nigeria [4,5,[16][17][18] and India. [11,19] In contrast, Ray et al [20] and Pinto et al [21] reported female preponderance.…”
Section: Discussionsupporting
confidence: 93%
“…More than half (51.3%) of the neonates with birth injuries in the present study were delivered via normal vaginal delivery as was also observed in other parts of Nigeria, [4,5,[16][17][18] India, [11,19] and Iran. [12] Operative deliveries are usually declined by many women especially in the developing countries due to cultural and religious beliefs as well as its huge financial implications.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations